AN ANALYSIS OF CLASSROOM MANAGEMENT USED BY TEACHER IN TEACHING ENGLISH - Wahyuni, Sri; Akib, Erwin; Sujariati (FKIP Unismuh Makassar, 2023)
This research used a qualitative research design. The English teacher at SMAN 1 Enrekang's 11 IPA 1 grade served as the study's subject. In-depth interviews and observation were the research tools used to get the data. For both the interview and the field notes, the researcher utilized semi-structured questions. The five aspects of classroom management that were the focus of the study were discipline, rules and routines, relationships, engaged and motivated instruction, and physical design. The actual layout of the teacher's classroom had two separate seating configurations. The first arrangement was in tidy rows for when the teacher delivered lessons and made presentations. The second arrangement had separate tables set up for small group discussions. This demonstrated the teacher's flexibility in changing the seating position to accommodate various class activities. The teacher devised routines to encourage discipline and enthusiasm in the learning process, as well as a learning agreement with each student at the start of each lesson. The teacher used team-building exercises that required collaboration to reach a common objective as well as small group talks to encourage relationships among the students. In order to establish relationships with the pupils, the teacher also adopted a personal style, frequently encouraging them at the beginning of lessons and complimenting their efforts. The teacher used a variety of teaching tools, including a whiteboard for presentations and questioning and laptops and speakers for games, to keep the class interested and motivated.